Intensifying insulin regimen after basal insulin optimization in adults with type 2 diabetes: a 24‐week, randomized, open‐label trial comparing insulin glargine plus insulin glulisine with biphasic insulin aspart (LanScape). Issue 12 (4th September 2015) - Vora, J.; Cohen, N.; Evans, M.; Hockey, A.; Speight, J.; Whately‐Smith, C.
Abstract : Aim: To test the hypothesis that a 'basal plus' regimenadding once‐daily main‐meal fast‐acting insulin to basal insulin once dailywould be non‐inferior to biphasic insulin twice daily as assessed by glycated haemoglobin (HbA1c) concentration (predefined as ≤0.4%), but would provide superior treatment satisfaction. Methods: This open‐label trial enrolled adults to an 8‐ or 12‐week run‐in period, during which oral therapies except metformin were stopped and insulin glargine dose was titrated. Those with fasting glucose <7 mmol/l but HbA1c >7% (53 mmol/mol) were randomized to insulin glargine/glulisine once daily (n = 170) or insulin aspart/aspart protamine 30/70 twice daily (n = 165) for 24 weeks, with dose titration to glucose targets using standardized algorithms. Results: For HbA1c, the basal plus regimen was non‐inferior to biphasic insulin (least squares mean difference, 0.21%, upper 97.5% confidence limit 0.38%) meeting the predefined non‐inferiority margin of 0.4%. Treatment satisfaction (Diabetes Treatment Satisfaction Questionnaire change version and Insulin Treatment Satisfaction Questionnaire total scores) significantly favoured basal plus. No difference was observed between the basal plus and the biphasic insulin groups in responders (HbA1c <7%, 20.6 vs 27.9%; p = 0.12), weight gain (2.06 vs 2.50 kg; p = 0.2), diabetes‐specific quality of life (Audit of Diabetes‐Dependent Quality of Life average weighted impact (AWI) score) and generic health status (five‐dimension European Quality of Life questionnaire). Overall hypoglycaemia rates were similar between groups (15.3 vs 18.2 events/patient‐year; p = 0.22); nocturnal hypoglycaemia was higher with the basal plus regimen (5.7 vs 3.6 events/patient‐year; p = 0.02). Conclusion: In long‐standing type 2 diabetes with suboptimal glycaemia despite oral therapies and basal insulin, the basal plus regimen was non‐inferior to biphasic insulin for biomedical outcomes, with a similar overall hypoglycaemia rate but more nocturnal events.